Assessment of the standard of municipal housing in a small town on the example of Twardogóra and Chocianów - Stettner, Milena (Budownictwo i Architektura / Civil and Architectural Engineering, 2018)
The condition of multi-family housing development depends on the town’s policy regarding the shaping of the communal resources. This is noticeable compared to the availability and technical standards of buildings. The author analyzes the directions of spatial development of the municipality and compares it with detailed evaluation of multi-family housing development in selected small towns up to 10.000 inhabitants: Chocianów and Twardogóra (located in the Lower Silesian Voivodship) – towns presenting the idea of maintaining large housing stock and thus controlling the development of housing. The article presents one of the stages of the research project – a detailed inventory of municipal property and analysis of planning documents in two small towns with a similar housing policy, population size, without the infl uence of the metropolitan city – which aims to create an optimal model of municipal housing development in the downtown of small towns up to 10,000 inhabitants in the Lower Silesian Voivodship.